DESIGN OF MSMEs DEVELOPMENT THROUGH PROFIT SHARING SCHEMES - Afkar, Taudlikhul; Purwanto, Teguh; Fauziyah, Fauziyah; Hariawan, Ferry; Istikhoroh, Siti (Jurnal Ilmu Sosial dan Humaniora, 2021)
The purpose of this study is to find the design of Micro, Small, and Medium Enterprises (MSMEs) development through profit-sharing schemes seen from the perspective of MSMEs actors in East Java - Indonesia. This research was conducted in East Java, Indonesia, selecting research locations carried out randomly and then determining the respondents proportionally. Respondents in this study were 220 MSMEs actors using the proportional random sampling technique. The data analysis technique used is warped partial least square to look for the design partially and through intervening. This study uses mudarabah financing and musharakah financing as exogenous variables, principles of profit-sharing distribution as intervening variables, and development of MSMEs as endogenous variables. The findings in this study are the contribution of profit-sharing distribution as an intervening variable in the development of MSMEs through the mudarabah financing scheme and the musharakah financing with the dominance of the musharakah financing. The ideal design of the development of MSMEs is the use of mudarabah financing and musharakah financing by applying the profit-sharing distribution principle following the principles of Islamic Sharia.